Our least important asset : why the relentless focus on finance and accounting is bad for business and employees - Cappelli, Peter (Ascent Audio, 2023)
"Real wages have stagnated or declined for most workers, job insecurity has increased, and retirement income is uncertain. Why have jobs gotten so much worse? As Peter Cappelli argues, these issues and others stem from the logic of financial accounting and its fundamental flaws in dealing with human capital. Financial accounting views employee costs as fixed costs that cannot be reduced and fails to account for the costs of bad employees and poor management. The simple goal of today's executives is to drive down employment costs, even if it raises costs elsewhere. In Our Least Important Asset, Cappelli argues that the financial accounting problem explains many puzzling practices in contemporary management-employers' emphasis on costs per hire over the quality of hires, the replacement of regular employees with ""leased"" workers, the shift to unlimited vacations, and the transition of hiring responsibilities from professional recruiters to more expensive line managers. In the process, employers undercut all the evidence about what works to improve the quality, productivity, and creativity of workers. Drawing on decades of experience and research, Cappelli provides a comprehensive and insightful critique of the modern workplace where the gaps in financial accounting make things worse for everyone, from employees to investors."